Risk of malaria in young children after periconceptional iron supplementation - Sabine Gies; Stephen A. Roberts; Salou Diallo; Olga M. Lompo; Halidou Tinto; Bernard J. Brabin (Wiley, 2021)
Abstract This study in Burkina Faso investigated whether offspring of young mothers who had received weekly periconceptional iron supplementation in a randomised controlled trial were at increased risk of malaria. A child safety survey was undertaken in the peak month of malaria transmission towards the end of the trial to assess child iron biomarkers, nutritional status, anaemia and malaria outcomes. Antenatal iron biomarkers, preterm birth, fetal growth restriction and placental pathology for malaria and chorioamnionitis were assessed. Data were available for 180 babies surviving to the time of the survey when their median age was 9 months. Prevalence of maternal iron deficiency in the last trimester based on low body iron stores was 16%. Prevalence of active placental malaria infection was 24.8%, past infection 59% and chorioamnionitis 55.6%. Babies of iron supplemented women had lower median gestational age. Four out of five children ≥ 6 months were iron deficient, and 98% were anaemic. At 4 months malaria prevalence was 45%. Child iron biomarkers, anaemia and malaria outcomes did not differ by trial arm. Factors associated with childhood parasitaemia were third trimester C‐reactive protein level (OR 2.1; 95% CI 1.1-3.9), active placental malaria (OR 5.8; 1.0-32.5, P = 0.042) and child body iron stores (OR 1.13; 1.04-1.23, P = 0.002). Chorioamnionitis was associated with reduced risk of child parasitaemia (OR 0.4; 0.1-1.0, P = 0.038). Periconceptional iron supplementation of young women did not alter body iron stores of their children. Higher child body iron stores and placental malaria increased risk of childhood parasitaemia.